1997
DOI: 10.1152/ajpheart.1997.272.4.h2023
|View full text |Cite
|
Sign up to set email alerts
|

A fiber matrix model for the filtration through fenestral pores in a compressible arterial intima

Abstract: We advance a new hypothesis to explain the changes in hydraulic conductivity of an intact artery wall with transmural pressure previously observed by Tedgui and Lever [Am. J. Physiol. 247 (Heart Circ. Physiol. 16): H784-H791, 1984] and Baldwin and Wilson [Am. J. Physiol. 264 (Heart Circ. Physiol. 33): H26-H32, 1993]. This hypothesis suggests that compaction due to pressure loading of the proteoglycan matrix in the arterial intima near fenestral pores of the internal elastic lamina (IEL) leads to a narrowing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 0 publications
5
61
1
Order By: Relevance
“…Of primary importance is whether transmural convection is very different and, thereby, transports different amounts of macromolecules into the walls of the PA and the IVC than into the aorta. The detailed measurements of L p for the aorta will complete a consistent set of data, all taken from the rat, for the model of Huang et al (16). It will also demonstrate whether the behavior of L p with pressure and endothelial denudation in rabbit aorta, attributed to intimal compression, also occurs in rat aorta.…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…Of primary importance is whether transmural convection is very different and, thereby, transports different amounts of macromolecules into the walls of the PA and the IVC than into the aorta. The detailed measurements of L p for the aorta will complete a consistent set of data, all taken from the rat, for the model of Huang et al (16). It will also demonstrate whether the behavior of L p with pressure and endothelial denudation in rabbit aorta, attributed to intimal compression, also occurs in rat aorta.…”
mentioning
confidence: 58%
“…Kim and Tarbell (22) attempted to explain the trend with a wall compaction hypothesis that invoked a variation of void fraction with distance into the wall. Huang et al (16) constructed a theory based on a large observed disparity in matrix structure and void volume between the intima (ϳ90% void for albumin) and media (a few percent void for albumin) (37). Their theory suggested that the intima easily compresses under pressure until its stiff collagen matrix carries the load and allows no further compression, but the dense media is nearly incompressible at these pressures.…”
Section: Shape Of the L P -⌬P Curvementioning
confidence: 99%
See 2 more Smart Citations
“…The PA intima pressure P SI lies above the aorta P SI . This indicates that the flow resistance due to the endothelium plus SI, including effects of SI compression and IEL fenestral blockage (22,24), contribute a smaller fraction of the total wall resistance in the PA than the aorta. [The statement of Shou et al (45) * are remarkably similar near the cleft, despite the vessels' very different ⌬P* and total wall L pt * .…”
Section: Pressure Distributionmentioning
confidence: 99%